2006
DOI: 10.1051/0004-6361:20066195
|View full text |Cite
|
Sign up to set email alerts
|

On theλ Bootis spectroscopic binary hypothesis

Abstract: Context. It is still a matter of debate whether the group of λ Bootis stars have been homogeneously defined. A widely discussed working hypothesis postulates that two apparent, solar-abundant stars of an undetected spectroscopic binary system mimic a single metal-weak spectrum thus preventing any reliable analysis of the group characteristics. Aims. We investigate whether the proposed spectroscopic binary model can explain the observed abundance pattern as well photometric metallicity indices and what the perc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
(33 reference statements)
1
14
3
Order By: Relevance
“…Stütz & Paunzen (2006) Venn & Lambert (1990), though those authors derived slightly different T eff (8750 K) and log g (4.0) compared to our values of 8495 K and 3.90. λ Boo exhibits absorption near λ 4479 Å (Fig. 4).…”
Section: λ Boo = Hd 125162contrasting
confidence: 91%
See 1 more Smart Citation
“…Stütz & Paunzen (2006) Venn & Lambert (1990), though those authors derived slightly different T eff (8750 K) and log g (4.0) compared to our values of 8495 K and 3.90. λ Boo exhibits absorption near λ 4479 Å (Fig. 4).…”
Section: λ Boo = Hd 125162contrasting
confidence: 91%
“…As in 21 LMi, the photospheric K line is strong enough to mask any small absorption feature that might also be present. Stütz & Paunzen (2006) also found no evidence for binarity from their statistical study of photometric indices.…”
Section: Lmi = Hd 87696mentioning
confidence: 95%
“…We then used state-of-the-art pulsation models to characterize the (in)stability properties. From this analysis we conclude that if the stars are still on the main sequence, which is the most accepted hypothesis (Stütz & Paunzen 2006), they are not intrinsically metal-weak. If they are beyond the terminal-age main sequence, the results are ambiguous.…”
Section: O N C L U S I O Nmentioning
confidence: 66%
“…A recent discussion of this hypothesis was presented by Stütz & Paunzen (2006). They concluded that at least some of these types of stars could be unsolved binary systems.…”
Section: Tablementioning
confidence: 99%